Characterization of single reed mouthpiece interaction in quasi-static regime - Gazengel Bruno; Dalmont Jean-Pierre; Gaillard Amélie; Brasseur Emmanuel; Taillard Pierre-André (Acta Acustica)
This paper describes an experimental measurement setup for the characterization of single-reed mouthpiece interaction under quasi-static conditions. Measurement leads to the estimation of the nonlinear characteristics, establishing the relation between pressure drop across the reed channel and the jet cross-section. Measurements with various lip forces show that the resultant nonlinear characteristics can be described by a single nonlinear characteristic linking the generalized pressure and the jet cross-section. This generalized pressure is the sum of the pressure drop and the lip pressure, defined as the lip force divided by an equivalent lip surface determined for each reed. The nonlinear characteristic is then modeled as a function depending on three parameters: the opening at rest, the linear stiffness for low pressures, and the “elbow pressure,” which allows to make the link between the two affine parts of the function. The characterization of 24 tenor saxophone reeds shows that the model fits the experimental characteristics with an inaccuracy that can be considered as a supplementary parameter for the reed. Finally, the reeds can be characterized with with only five parameters, the inaccuracy, the lip equivalent surface and the three parameters of the nonlinear model. First results suggest that equivalent lip surface and inaccuracy depends on the reed type while reed opening at rest and linear stiffness depends on the reed.